Reactions between country rock xenoliths and the magma of Uitkomst Complex, with implications for the origin of the sulphide mineralization - Maier, Wolfgang D. (University of Pretoria, 2013)
Dissertation (MSc (Geology))--University of Pretoria, 2008.